On general characterization of Young measures associated with Borel functions - Grzybowski, Andrzej Z.; Puchała, Piotr (Archives of Control Sciences, 2026)
We prove that the Young measure associated with a Borel function $f$ is a probability distribution of the random variable $f(U)$, where $U$ has a uniform distribution on the domain of $f$. Examples of specific applications of the main result, including Monte Carlo method of simulation of Young measures, are presented with comments.